The Relationship Between Special Economic Zones and Economic Growth and Welfare: Empirical Evidence from Regencies and Cities in Indonesia - Sa'diah, Minarti; Khoirunurrofik, Khoirunurrofik (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality — Special economic zones (SEZs) are a government policy aimed at increasing the economic growth in certain areas. Increasing economic growth in an area is important to improve community welfare. Research Objective — From the employment side, welfare can be measured through the unemployment rate. This research aims to analyze the relationship between SEZs and economic growth and community welfare at the regency/city level as measured by unemployment rate. Research Methods — This research analyzed regencies/cities in 14 provinces that have SEZ, with the research conducted over the period of 2010 to 2021. Analysis was carried out using the two-stage least squares (2SLS) method. Empirical Results — The results of the research showed that SEZs exhibited a significant positive relationship with regional economic growth, while SEZs showed an insignificant relationship with regencies/cities welfare as measured by unemployment rate indicator. Implications — The findings of the research suggest that the implementation of SEZs can be maintained and continued. The regional governments can take advantage of SEZ by strengthening infrastructure and collaborating with the central government to increase the competence of local labor.